2015
DOI: 10.1016/j.polymer.2015.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Fiber structure development in PS/PET sea-island conjugated fiber during continuous laser drawing

Abstract: The effect of draw ratio, molecular weight, and sea-island conjugated spinning with a polystyrene component on the fiber structure development of PET during laser drawing was analyzed by in-situ measurements with a 0.1 ms time resolution using an ultra-high luminance X-ray beam generated from a synchrotron equipped with an undulator. The fiber temperature increased from 120 o C to 160-220 o C during the structure development process. By drawing the higher molecular weight PET to a higher draw ratio, a larger a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 32 publications
(42 reference statements)
0
13
0
Order By: Relevance
“…The melting and mixing process can generate morphologies ranging from dispersed drops to fibers to lamella to co-continuous structures [33], see Figure 2. The initial morphology of immiscible polymer blend fibers is usually represented as a droplet-matrix or fibril-matrix morphology [31,32,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. The strategy to produce lamellae and other morphologies is more difficult than that required for the droplet-matrix morphology since the interfacial tension tends to minimize the surface of the second phase [7].…”
Section: Morphology Development Along the Spinning Linementioning
confidence: 99%
“…The melting and mixing process can generate morphologies ranging from dispersed drops to fibers to lamella to co-continuous structures [33], see Figure 2. The initial morphology of immiscible polymer blend fibers is usually represented as a droplet-matrix or fibril-matrix morphology [31,32,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. The strategy to produce lamellae and other morphologies is more difficult than that required for the droplet-matrix morphology since the interfacial tension tends to minimize the surface of the second phase [7].…”
Section: Morphology Development Along the Spinning Linementioning
confidence: 99%
“…The average position of the necking point and its fluctuation width were determined by analysis of still images taken from the video movie recorded during each measurement. The resolution time was calculated by a reported method [18] by the position resolution, which was calculated from the fluctuation width of the necking point (0.09-0.20 mm), length of the necking point (0.12-0.31 mm), and width of the X-ray beam (0.05 mm). The obtained time resolution was 0.09-0.18 ms.…”
Section: Online Measurementmentioning
confidence: 99%
“…For PET/polystyrene (PS) conjugated spun fibers, no crystallization induction time was observed after drawing [18]. The authors suggested that the PET component did not bear the drawing stress;…”
Section: Crystallization Ratementioning
confidence: 99%
See 1 more Smart Citation
“…However, in the postprocessing step for the MSLB, it is necessary to remove the sea component using toluene (unfigured sea-island fibers) or sodium hydroxide (figured sea-island fibers), which brings serious environmental pollution and waste of resources. 15 In contrast to the sea-island fibers, segmented pie fibers are usually split by mechanical treatment (needle punching, hydroentangling, ultrasonic, stretching) and have several advantages, such as high mechanical properties, being non-polluting and being easy to process; however, their nonwoven fabric still suffers from low permeability, poor tear resistance and hard softness, since the split fibers have relatively large diameter, filament structure and wedge cross-section, tending to pack tightly. To date, with the development of spinning technology, electrostatic spinning is considered as the most effective method for fabricating nanofibers with a diameter of <100 nm.…”
mentioning
confidence: 99%